Machinability investigation and cost estimation during finish dry hard turning of AISI 4340 steel with untreated and cryo treated cermet inserts - Anshuman Das; Saroj Kumar Patel; Bibhuti Bhusan Biswal; Sudhansu Ranjan Das (Сверхтвердые материалы, 2019)
For higher tool life of cutting inserts cryogenic treatment is considered as the most prominent method but no substantial researches have been found concerning the impact of cryogenic treatment on cermet inserts especially in hard turning. Therefore, in the present experimental investigation, the comparative assessment of various responses such as cutting force, flank wear, crater wear, chip morphology and surface roughness were carried out during machining of hardened steel with both untreated and cryo treated cermet ins hard turning erts under dry cutting condition. Lastly, the input variables were optimized using Response surface methodology (RSM) to evaluate the tool life for the economic analysis. The experimental result demonstrated that the uncoated deep cryo treated with tempered cermet insert delivered better results in comparison to other cermet inserts. According to cost analysis, uncoated and deep cryo treated with tempered cermet insert was found to be the most economical among other cermet inserts at the optimum cutting condition.